(untitled) (East West Medical College Journal, 2026)
Background: Maternal hypotension is one of the common complications after spinal anesthesia for cesarean delivery, resulting in adverse maternal and fetal outcomes. The selection of the most efficient treatment is one of the main challenges in obstetric cases. Prompt treatment of hypotension with intravenous vasopressor is necessary to avoid these maternal and fetal effects. This study will set to compare phenylephrine’s effectiveness in treating subarachnoid block induced hypotension in relation to ephedrine during elective lower uterine cesarean section (LUCS) under the subarachnoid block (SAB). Objectives: The study objective is to compare the effects of a bolus dose of ephedrine versus phenylephrine in treating subarachnoid block-induced hypotension during elective lower uterine cesarean section. Study of Place: Department of Anesthesiology & Intensive Care Unit (ICU), East West Medical College, Dhaka, Bangladesh. Study period: From September 2023 to February 2024. Study design: Prospective, randomized, double-blinded trial Method: The study population was women undergoing lower uterine cesarean section (LUCS) who fulfilled the selection criteria. The study sample was selected by prospective, randomized, double-blinded trial. Ninety patients were enrolled in this study and allocated equally into Group A (Ephedrine administered group) and Group B (Phenylephrine administered group). All relevant data were collected and analyzed with a statistical package of social science (SPSS) version 23 software, and all the statistical tests were considered significant when p value <0.05. Results: The study results showed that after using a vasopressor and its response in mean arterial pressure of the patient at 2nd, 4th, and 6th minutes were greater in the phenylephrine group in comparison to the ephedrine group, and it was statistically significant (p value 0.043, 0.038, and 0.049, respectively). Vasopressor response to mean heart rate of the patient at 2nd, 4th, 6th and 8th minutes was lesser in the phenylephrine group than the ephedrine group, and it was also statistically significant (0.036, 0.028, 0.018, and 0.048, respectively). However, the study results comparing two groups revealed no significance concerning demographic variables, i.e., Mean age ± SD, Body mass index (BMI) Mean ± SD (p value 0.523 and 0.567, respectively). The fetal response measured as APGAR scores at 1st and 5th minutes, between two groups, were not significant (p value 0.096 and 0.427, respectively). The comparison between the two groups to determine the maternal respiratory rate and percentage saturation of oxygen (SpO2) were not significant. Conclusion: The study concluded that the uses of phenylephrine compared to ephedrine were relatively better to raise the mean arterial pressure for subarachnoid block-induced hypotension in lower uterine cesarean section (LUCS). EWMCJ Vol. 14, No. 2, July 2026: 223-229